1990
DOI: 10.1182/blood.v75.12.2267.bloodjournal75122267
|View full text |Cite
|
Sign up to set email alerts
|

Long- and short-lived murine hematopoietic stem cell clones individually identified with retroviral integration markers

Abstract: The proliferative longevity of totipotent hematopoietic stem cells (THSC) is a limiting factor in normal hematopoiesis and in therapy by cell- or gene-replacement, but has not yet been ascertained. We have followed the long-term fate of individual clones of mouse THSC from fetal liver or adult bone marrow, after labeling in culture, followed by engraftment and serial transplantation in unirradiated W/Wv-C57BL/6 hosts. The ancestor cell of each clone and its mitotic progeny were uniquely identifiable retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Assuming that a representative proportion of all HSCs was transduced by in vivo injection, a surprisingly high number of more than 400 to several thousand HSC clones simultaneously carried steady‐state hematopoiesis. In contrast, only a limited number of ex vivo manipulated stem cell clones have been reported to maintain hematopoiesis following transplantation [7, 8, 13]. Pretransplantation conditioning may contribute to this apparent difference, as stroma and endothelial cell damage may alter the HSC niche function leading to a limited, only partial refilling of the stem cell compartment [27, 32–35, 58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that a representative proportion of all HSCs was transduced by in vivo injection, a surprisingly high number of more than 400 to several thousand HSC clones simultaneously carried steady‐state hematopoiesis. In contrast, only a limited number of ex vivo manipulated stem cell clones have been reported to maintain hematopoiesis following transplantation [7, 8, 13]. Pretransplantation conditioning may contribute to this apparent difference, as stroma and endothelial cell damage may alter the HSC niche function leading to a limited, only partial refilling of the stem cell compartment [27, 32–35, 58].…”
Section: Discussionmentioning
confidence: 99%
“…In retrospect, limitations in the sensitivity of detection of active clones at that time may have contributed to this interpretation. Strong evidence for a lifelong contribution of individual self‐renewing HSC to blood cell production after transplantation [11–13] favors an alternative model. Studies in cats [14], mice [15], and immunodeficient mice engrafted with human hematopoietic transplants [16] demonstrated that the initial phase of hematopoietic recovery after transplantation is driven by many short‐lived clones, whereas long‐term hematopoiesis derives from a smaller number of stable stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…The common expression of c-Kit and/or Sca-1 and the SP phenotype between stem cells of different murine tissues suggests that populations enriched for these markers might include putative adult pluripotent stem cells. Additional markers are needed so that the relevant stem cell populations can be prospectively identified and tagged for in vivo tracking [105,106,107,108]. The degree of restoration of function is a central issue that has obvious ramifications for the future success of stem cellbased therapeutics.…”
Section: Important Questions Remaining To Be Addressedmentioning
confidence: 99%
“…Nonetheless, although MLV is known to transform primate cells when allowed to replicate (22), in view of a multistep mechanism of malignant transformation in humans (23,24), the risk of leukemogenesis from replicationdefective MLV-based gammaretroviral vectors (16) was believed to be low. Similarly, clonal dominance -the predominant occurrence of a few retroviral vector-marked HSC-derived hematopoietic clones following bone marrow transplantation -had been thought to be a natural property of hematopoiesis (25)(26)(27). However, insertion site analysis in recent preclinical and clinical gene transfer studies has indicated that retroviral integration may influence this process by activating genes involved in growth control -such as the Evi1 oncogene (8,13,14,28) leading in some cases to selective nonmalignant clonal outgrowth (9,15).…”
Section: Introductionmentioning
confidence: 99%
“…Retroviral vectors having this design are referred to as 'self-inactivating' (SIN) vectors (40)(41)(42)(43). With the exception of our HHAM vector platform (26,27,41), the titers of the initial versions of most SIN gammaretroviral vectors were too low to be of utility for HSC gene transfer. However, recent advances have resulted in SIN gammaretroviral vector titers approaching those of conventional LTR vectors (44)(45)(46).…”
Section: Introductionmentioning
confidence: 99%